2008
DOI: 10.1007/s10585-008-9147-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of 18F-FDG uptake in primary osteosarcoma after but not before chemotherapy: a possible association with autocrine motility factor/phosphoglucose isomerase expression

Abstract: Response to neoadjuvant chemotherapy is a significant prognostic factor for osteosarcoma (OS). 18-F-fluorodeoxy-D: -glucose (FDG) positron emission tomography (PET) is a noninvasive imaging modality that correlates with histological grading in musculoskeletal sarcomas. To determine the prognostic value of FDG PET in patients receiving chemotherapy, 13 patients were evaluated by FDG-PET, and followed for more than 4 years. FDG PET standardized uptake values before (SUV1) and after (SUV2) chemotherapy were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
5
14
0
Order By: Relevance
“…Many of our findings, such as the association between tumor necrosis and outcome (2,4,9-11) and the association of worse survival with high metabolic activity in the chemotherapy-naïve tumor (17) and with high metabolic activity after chemotherapy (17), all confirm the conclusions of prior studies that 18 F-FDG PET accurately reflects response of osteosarcoma to chemotherapy. Despite the small number of deaths and relatively short follow-up, our study results are similar to a recently published study with follow-up periods of more than 4 y that showed that survival is associated with SUV max after chemotherapy (21).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many of our findings, such as the association between tumor necrosis and outcome (2,4,9-11) and the association of worse survival with high metabolic activity in the chemotherapy-naïve tumor (17) and with high metabolic activity after chemotherapy (17), all confirm the conclusions of prior studies that 18 F-FDG PET accurately reflects response of osteosarcoma to chemotherapy. Despite the small number of deaths and relatively short follow-up, our study results are similar to a recently published study with follow-up periods of more than 4 y that showed that survival is associated with SUV max after chemotherapy (21).…”
Section: Discussionsupporting
confidence: 90%
“…Few published studies assess the utility of 18 F-FDG PET in the evaluation of the response of osteosarcoma to neoadjuvant chemotherapy (16)(17)(18)(19)(20)(21). Many of our findings, such as the association between tumor necrosis and outcome (2,4,9-11) and the association of worse survival with high metabolic activity in the chemotherapy-naïve tumor (17) and with high metabolic activity after chemotherapy (17), all confirm the conclusions of prior studies that 18 F-FDG PET accurately reflects response of osteosarcoma to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implications for limb salvage surgery were described because such complex tumor resection procedures might not be considered in nonresponders (52). Others have recently shown similar results for 18 F-FDG imaging in osteosarcoma (53,54).…”
Section: F-fdg In Sarcoma Restaging and Treatment Responsesupporting
confidence: 58%
“…Sato et al [6] evaluated a series of 13 patients by measuring the sarcoma SUV max before and after the neoadjuvant chemotherapy and correlated them with the expression of metastasis-related glycolytic enzyme and autocrine motility factor/phosphoglucose isomerase by immuno-histochemical examination in surgically excised tumours. The follow-up was 4 years.…”
Section: Pet and The Prediction Of Prognosismentioning
confidence: 99%